Implant-retained auricular prostheses: a clinical challenge. Issue 5 (May 2016) - Arora, V.; Sahoo, N.K.; Gopi, A.; Saini, D.K.
Abstract: Microtia, malformation, deformity, and partial or complete loss of the pinna may be due to various congenital or acquired factors. In adult patients, surgical reconstruction of the missing pinna is difficult and the results are often far from satisfactory. An implant-retained auricular prosthesis is a suitable alternative. A retrospective study of eight patients treated with implant-retained auricular prostheses was performed. For each missing pinna, three titanium implants were placed in the temporal bone. After 6 months of osseointegration, the implants were loaded. Four cases were rehabilitated with a magnet-retained prosthesis and the remaining four with a bar and clip retained prosthesis. There were six male and two female patients with an average age of 30.62 years. Seven patients had unilateral absence of the pinna and one had bilateral absence. The loss was due to trauma in four patients and to burn in one patient, and three had congenital absence. A total 27 implants were placed, 12 on the right side and 15 on the left. The average post-rehabilitation follow-up was 21 months. Peri-implant tissue reactions were observed at two sites. The implant-retained auricular prosthesis is an alternative treatment approach with good retention and patient satisfaction. Long-term follow-up is required to assess delayed complications.